2016
DOI: 10.1109/tap.2016.2593931
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Dual-Band Reflection-Mode Circular Polarizers Using Dual-Layer Rectangular Frequency Selective Surfaces

Abstract: A new kind of dual-band reflection-mode circular polarizers (RMCPs) is introduced with wide bandwidth and wide-view at the operating frequencies. The proposed RMCPs are based on dual-layer rectangular patches on both sides of a substrate, separated by a foam or air layer from the ground plane. Required TE susceptance of the first layer patches to produce circular polarization is calculated using the equivalent transmission line model. Dimensions of the RMCP are obtained using parametrical study for the two fre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 26 publications
(47 reference statements)
0
9
0
Order By: Relevance
“…In addition, the components of these systems often have multiple choices initially. As an example, an improvement for RMCPs can be found in [49]. The next alternative in this system is the type of parabolic reflector and hyperbolic sub-reflector.…”
Section: Innovative Ideas For Antenna Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the components of these systems often have multiple choices initially. As an example, an improvement for RMCPs can be found in [49]. The next alternative in this system is the type of parabolic reflector and hyperbolic sub-reflector.…”
Section: Innovative Ideas For Antenna Systemsmentioning
confidence: 99%
“…In addition, the components of these systems often have multiple choices initially. As an example, an improvement for RMCPs can be found in [49].…”
Section: Innovative Ideas For Antenna Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other structures also can be used for RMCPs with similar methods of operation. For example, L‐shaped patches and multilayer metamaterials have been used for wideband applications …”
Section: Introductionmentioning
confidence: 99%
“…By introducing some kind of asymmetric degeneracy separation unit in the structure, the two resonant modes can be excited with two orthogonal linear polarizations with nearly equal amplitude and 90°phase difference to achieve CP characteristics [1]. Numerous studies for antennas of single-feed circular polarization can be found in the literature [2][3][4][5][6][7]. Another method is to excite two resonant modes to achieve circular polarization by dual feed.…”
Section: Introductionmentioning
confidence: 99%